Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1:
a: =>3x=6
=>x=2
b: =>4x=16
=>x=4
c: =>4x-6=9-x
=>5x=15
=>x=3
d: =>7x-12=x+6
=>6x=18
=>x=3
2:
a: =>2x<=-8
=>x<=-4
b: =>x+5<0
=>x<-5
c: =>2x>8
=>x>4
`Answer:`
Bài 1:
a) \(7+2x=22-3x\)
\(\Leftrightarrow2x+3x=22-7\)
\(\Leftrightarrow5x=15\)
\(\Leftrightarrow x=3\)
b) \(8x-3=5x+12\)
\(\Leftrightarrow8x-5x=12+3\)
\(\Leftrightarrow3x=15\)
\(\Leftrightarrow x=5\)
c) \(x-12+4x=25+2x-1\)
\(\Leftrightarrow x-12+4x-25-2x+1=0\)
\(\Leftrightarrow\left(x+4x-2x\right)+\left(1-12-25\right)=0\)
\(\Leftrightarrow3x-36=0\)
\(\Leftrightarrow x=12\)
d) \(x+2x+3x-19=3x+5\)
\(\Leftrightarrow6x-19=3x+5\)
\(\Leftrightarrow6x-3x=5+19\)
\(\Leftrightarrow3x=24\)
\(\Leftrightarrow x=8\)
Bài 2:
a) \(\left(2,3x-6,9\right)\left(0,1x+2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2,3x-6,9=0\\0,1x+2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=3\\x=-20\end{cases}}}\)
b) \(\left(2x+7\right)\left(x-5\right)\left(5x+1\right)=0\)
\(\Leftrightarrow2x+7=0\text{ hoặc }x-5=0\text{ hoặc }5x+1=0\)
\(\Leftrightarrow x=-\frac{7}{2}\text{ hoặc }x=5\text{ hoặc }x=-\frac{1}{5}\)
c) \(\left(4x+2\right)\left(x^2+1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}4x+2=0\\x^2+1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-\frac{1}{2}\\x^2=-1\text{(Loại)}\end{cases}}}\)
d) \(\left(x^2-4\right)+\left(x-2\right)\left(3-2x\right)=0\)
\(\Leftrightarrow x^2-4+\left(3x-2x^2-6+4x\right)=0\)
\(\Leftrightarrow x^2-4=\left(-2x^2+7x-6\right)=0\)
\(\Leftrightarrow x^2-4-2x^2+7x-6=0\)
\(\Leftrightarrow-x^2+7x-10=0\)
\(\Leftrightarrow x^2-5x-2x+10=0\)
\(\Leftrightarrow x.\left(x-5\right)-2.\left(x-5\right)=0\)
\(\Leftrightarrow\left(x-5\right).\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\x-2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=5\\x=2\end{cases}}}\)
a: \(\dfrac{x+10}{4x-8}\cdot\dfrac{4-2x}{x+2}\)
\(=\dfrac{x+10}{4\left(x-2\right)}\cdot\dfrac{-2\left(x-2\right)}{x+2}=\dfrac{-\left(x+10\right)}{2\left(x+2\right)}\)
b: \(\dfrac{1-4x^2}{x^2+4x}:\dfrac{2-4x}{3x}\)
\(=\dfrac{\left(2x-1\right)\left(2x+1\right)}{x\left(x+4\right)}\cdot\dfrac{3x}{2\left(x-2\right)}\)
\(=\dfrac{3\left(2x-1\right)\left(2x+1\right)}{2\left(x-2\right)\left(x+4\right)}\)
c: \(=\dfrac{4y^2}{7x^4}\cdot\dfrac{35x^2}{-8y}=\dfrac{5}{x^2}\cdot\dfrac{-1}{2}\cdot y=\dfrac{-5y}{2x^2}\)
d: \(=\dfrac{\left(x-2\right)\left(x+2\right)}{3\left(x+4\right)}\cdot\dfrac{x+4}{2\left(x-2\right)}=\dfrac{x+2}{6}\)
a: \(\dfrac{x^2-5x+6}{x^2+7x+12}:\dfrac{x^2-4x+4}{x^2+3x}\)
\(=\dfrac{\left(x-2\right)\left(x-3\right)}{\left(x+3\right)\left(x+4\right)}\cdot\dfrac{x\left(x+3\right)}{\left(x-2\right)^2}\)
\(=\dfrac{x\left(x-3\right)}{\left(x-2\right)\left(x+4\right)}\)
b: \(\dfrac{x^2+2x-3}{x^2+3x-10}:\dfrac{x^2+7x+12}{x^2-9x+14}\)
\(=\dfrac{\left(x+3\right)\left(x-1\right)}{\left(x+5\right)\left(x-2\right)}\cdot\dfrac{\left(x-2\right)\left(x-7\right)}{\left(x+3\right)\left(x+4\right)}\)
\(=\dfrac{\left(x-1\right)\left(x-7\right)}{\left(x+5\right)\left(x+4\right)}\)
\(a)x^3-\frac{x}{49}=0\)
\(\Leftrightarrow x\left(x^2-\frac{1}{7^2}\right)=0\)
\(\Leftrightarrow x=0\)Hoặc \(x^2-\frac{1}{7^2}=0\)
TH1: \(x\left(x^2-\frac{1}{7^2}\right)=0\\ x=\frac{0}{x^2-\frac{1}{7^2}}\\ \Leftrightarrow x=0\)
TH2: \(x\left(x^2-\frac{1}{7^2}\right)=0\\ x^2-\frac{1}{7^2}=\frac{0}{x}\\ x^2=0+\frac{1}{7^2}\\ x^2=\frac{1}{7^2}\\ x^2=\left(\frac{1}{7}\right)^2\\ \Leftrightarrow x=\frac{1}{7}\)
Vậy \(x=0\)Hoặc \(x=\frac{1}{7}\)
a) x3 - x/49 = 0
<=> x(x2 - 1/49) = 0
<=> x = 0 hoặc x2 - 1/49 = 0
<=> x = 0 hoặc x = +1/7
b) x2 - 7x + 12 = 0
<=> (x - 3)(x - 4) = 0
<=> x - 3 = 0 hoặc x - 4 = 0
<=> x = 3 hoặc x = 4
c) 4x2 - 3x - 1 = 0
<=> 4x2 + x - 4x - 1 = 0
<=> x(4x + 1) - (4x + 1) = 0
<=> (4x + 1)(x - 1) = 0
<=> 4x + 1 = 0 hoặc x - 1 = 0
<=> x = -1/4 hoặc x = 1
d) x3 - 2x - 4 = 0
<=> (x2 + 2x + 2)(x - 2) = 0
vì x2 + 2x + 2 khác 0 nên:
<=> x - 2 = 0
<=> x = 2
a: \(x^3-4x^2-x+4=0\)
=>\(\left(x^3-4x^2\right)-\left(x-4\right)=0\)
=>\(x^2\left(x-4\right)-\left(x-4\right)=0\)
=>\(\left(x-4\right)\left(x^2-1\right)=0\)
=>\(\left[{}\begin{matrix}x-4=0\\x^2-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=4\\x^2=1\end{matrix}\right.\Leftrightarrow x\in\left\{2;1;-1\right\}\)
b: Sửa đề: \(x^3+3x^2+3x+1=0\)
=>\(x^3+3\cdot x^2\cdot1+3\cdot x\cdot1^2+1^3=0\)
=>\(\left(x+1\right)^3=0\)
=>x+1=0
=>x=-1
c: \(x^3+3x^2-4x-12=0\)
=>\(\left(x^3+3x^2\right)-\left(4x+12\right)=0\)
=>\(x^2\cdot\left(x+3\right)-4\left(x+3\right)=0\)
=>\(\left(x+3\right)\left(x^2-4\right)=0\)
=>\(\left(x+3\right)\left(x-2\right)\left(x+2\right)=0\)
=>\(\left[{}\begin{matrix}x+3=0\\x-2=0\\x+2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-3\\x=2\\x=-2\end{matrix}\right.\)
d: \(\left(x-2\right)^2-4x+8=0\)
=>\(\left(x-2\right)^2-\left(4x-8\right)=0\)
=>\(\left(x-2\right)^2-4\left(x-2\right)=0\)
=>\(\left(x-2\right)\left(x-2-4\right)=0\)
=>(x-2)(x-6)=0
=>\(\left[{}\begin{matrix}x-2=0\\x-6=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2\\x=6\end{matrix}\right.\)
Bài 1:
a) Ta có: 7x+12=0
\(\Leftrightarrow7x=-12\)
hay \(x=-\frac{12}{7}\)
Vậy: \(x=-\frac{12}{7}\)
b) Ta có: 5x-2=0
\(\Leftrightarrow5x=2\)
hay \(x=\frac{2}{5}\)
Vậy: \(x=\frac{2}{5}\)
c) Ta có: 12-6x=0
\(\Leftrightarrow6x=12\)
hay x=2
Vậy: x=2
d) Ta có: -2x+14=0
⇔-2x=-14
hay x=7
Vậy: x=7
Bài 2:
a) Ta có: 3x+1=7x-11
⇔3x+1-7x+11=0
⇔-4x+12=0
⇔-4x=-12
hay x=3
Vậy: x=3
b) Ta có: 2x+x+12=0
⇔3x+12=0
⇔3x=-12
hay x=-4
Vậy: x=-4
c) Ta có: x-5=3-x
⇔x-5-3+x=0
⇔2x-8=0
⇔2x=8
hay x=4
Vậy: x=4
d) Ta có: 7-3x=9-x
⇔7-3x-9+x=0
⇔-2x-2=0
⇔-2x=2
hay x=-1
Vậy: x=-1
e) Ta có: 5-3x=6x+7
⇔5-3x-6x-7=0
⇔-9x-2=0
⇔-9x=2
hay \(x=\frac{-2}{9}\)
Vậy: \(x=\frac{-2}{9}\)
f) Ta có: 11-2x=x-1
⇔11-2x-x+1=0
⇔12-3x=0
⇔3x=12
hay x=4
Vậy: x=4
g) Ta có: 15-8x=9-5
⇔15-8x=4
⇔8x=11
hay \(x=\frac{11}{8}\)
Vậy: \(x=\frac{11}{8}\)
Bài 3:
a) Ta có: 0,25x+1,5=0
⇔0,25x=-1,5
hay x=-6
Vậy: x=-6
b) Ta có: 6,36-5,2x=0
⇔5,2x=6,36
hay \(x=\frac{159}{130}\)
Vậy: \(x=\frac{159}{130}\)
15-8x=9-5x
<=> 5x - 8x = 9 - 15
<=> -3x = -6
<=> x = 2
\(a,PT\Leftrightarrow3x=12\Leftrightarrow x=4\)
\(b,PT\Leftrightarrow4x=16\Leftrightarrow x=4\)
Câu c, d?
a) \(3x-12=0\)
\(\Leftrightarrow3x=0+12\)
\(\Leftrightarrow3x=12\)
\(\Leftrightarrow x=4\)
b)